جمالية السخرية في شعر أحمد مطر نماذج مختارة - بن شاعة, فاطيمة (كلية الأدب العربي والفنون, 2024)
السّخرية هي منهج فكري وطريقة اتبعها بعض الشعراء للتعبير عن معاناتهم وآلامهم، والكشف عن مظاهر الفساد والعنف في البلاد، وعن المفسدين والظالمين، نجد أنّ للسّخرية أساليب مختلفة ومتعددة كالمفارقة والرمز وغيرها، ويعد أحمد مطر شاعر مفارقات بامتياز. حيث استخدم المفارقة من خلال الألفاظ المتضادة وإبراز العيوب والاستهزاء بها.توظيف الرمز واستخدامه كوسيلة لتدعيم موقفه خاصة الرمز الطبيعي والرمز الحيواني، كما نجده استخدم أسلوب التضاد من خلال استخدام لفظتين متضادتين في سياق واحد، وأيضا أسلوب التكرار من خلال تكرار حرف أو كلمة أو جملة.من جمالية السّخرية في شعر أحمد مطر هي الكشف عن معاناته وآلامه، كما يكشف لنا الحكام الظالمين والمفسدين Sarcasm is an intellectual approach and a method followed by some poets to express their suffering and pain and reveal manifestations of corruption and the violence and the poor and the oppressors .We find that satire has many different methods such as irony symbolism and others Ahmed Matar is considered a poet of paradoxes par excellence as he used irony through contrasting words and highlighting faults and mocking them. Employing the symbol and using it as a means to support his position especially the natural symbol and the animal symbol. We also find him using the method of contrast by using two opposite words in one context and also the method of repeating a letter word or sentence One of the beauty of irony in Ahmed poetry is revealing his suffering and pain just as it reveals to us the corruptors and unjust rulers.
Keywords: السّخرية، الجمالية، الأسلوبية، الشعر العربي المعاصر، أحمد مطر; Irony. Aesthetic. stylistics. Contemporary Arabic poetry. Ahmed matter.